From gut to joint: the protective impact of Eubacterium rectale on rheumatoid arthritis - Liu, Xiaoyang; Wu, Ruihe; Fan, Yuxin; Qin, Kaili; Li, Baochen; Li, Xiaofeng; Gao, Chong; Wang, Caihong (Frontiers in Immunology, 2025)
BackgroundRheumatoid arthritis (RA) is a chronic autoimmune disease with a complex and diverse etiology. The onset of RA is closely associated with intestinal flora, which is essential for immune regulation.MethodsFecal samples of 22 healthy controls and 38 patients with newly diagnosed RA were used for performing 16S rRNA sequencing, microbiota diversity assessment, and functional enrichment analysis. Through integrative analysis of random forest feature selection and bidirectional Mendelian randomization (MR), Eubacterium rectale was prioritized as a key bacterial candidate associated with RA. Furthermore, E. rectale was used to treat the arthritis model mice by gavage treatment, and we evaluated joint inflammation and immune cell profile in mice. Finally, untargeted metabolomics was used to evaluate the changes in serum and fecal metabolites in the arthritis mouse model before and after E. rectale intervention.ResultsThe beta diversity of the intestinal flora exhibited significant differences between RA patients and healthy controls (HC). Functional enrichment analysis revealed that RA patients’ intestinal microbiota functions were enriched in pathways like genetic information processing and material metabolism. Further random forest model revealed E. rectale, Bacteroides, etc., and twelve genera with characteristic significance in RA patients. According to further MR analysis, Anaerostipes and E. rectale had a protective effect on RA, and reverse MR analysis showed no evidence of a causal relationship between these groups and RA. In vivo experiments showed that after the administration of E. rectale, the joint inflammation of the mice was relatively slight, the bone destruction and bone density of the joints improved, the proportion of Treg and follicular regulatory T cells (Tfr) cells increased, and the proportion of follicular helper T cells (Tfh) cells decreased. Metabolomic analysis revealed significant changes in both serum and fecal metabolites in mice with collagen-induced arthritis (CIA) compared with healthy controls. The changes in metabolites such as butyric acid were reversed after treatment with E. rectal.ConclusionThe study demonstrates that E. rectale has a protective effect on RA. E. rectale significantly attenuates joint inflammation in mouse models by may regulating the expression level of butyrate, ameliorating the Treg and Tfr/Tfh immune imbalance status, and re-establishing the immune tolerance. These findings serve as valuable references for future studies on the pathogenesis of RA and the development of new therapeutic approaches.